2016
DOI: 10.3791/52437
|View full text |Cite
|
Sign up to set email alerts
|

EPA Method 1615. Measurement of Enterovirus and Norovirus Occurrence in Water by Culture and RT-qPCR. II. Total Culturable Virus Assay

Abstract: A standardized method is required when national studies on virus occurrence in environmental and drinking waters utilize multiple analytical laboratories. The U.S Environmental Protection Agency's (USEPA) Method 1615 was developed with the goal of providing such a standard for measuring Enterovirus and Norovirus in these waters. Virus is concentrated from water using an electropositive filter, eluted from the filter surface with beef extract, and then concentrated further using organic flocculation. Herein we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Fout and Cashdollar (2016) indicated that USEPA Method 1615 may be adapted for the detection of adenoviruses (59). It is recommended to explore modifying existing methods with secondary concentration by PEG precipitation to uphold virus recovery and minimize inactivation during sample processing and detection by culture-based methods.…”
Section: Masclaux Et Al (mentioning
confidence: 99%
“…Fout and Cashdollar (2016) indicated that USEPA Method 1615 may be adapted for the detection of adenoviruses (59). It is recommended to explore modifying existing methods with secondary concentration by PEG precipitation to uphold virus recovery and minimize inactivation during sample processing and detection by culture-based methods.…”
Section: Masclaux Et Al (mentioning
confidence: 99%
“…The standard molecular methods with which the water industry may be familiar are based on quantitative polymerase chain reaction (qPCR); for example, the detection and quantification of Legionella spp./ L. pneumophila in environmental and recreational waters in the UK [12] or enterovirus, norovirus and enterococci in the USA [13, 14]. It is plausible that qPCR might overcome some of the limitations of microscopy for monitoring drinking water for Cryptosporidium, and capitalize on the presence of four sporozoites in each intact oocyst, increasing the number of targets by fourfold compared to oocyst microscopy.…”
Section: Introductionmentioning
confidence: 99%